2009
DOI: 10.1113/jphysiol.2008.168468
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle effects on sympathetic neural responses to upright tilt

Abstract: Young women are more susceptible to orthostatic intolerance than men, though the sex-specific pathophysiology remains unknown. As blood pressure (BP) is regulated through the baroreflex mechanism, we tested the hypothesis that baroreflex control of muscle sympathetic nerve activity (MSNA) during orthostasis is impaired in women and can be affected by the menstrual cycle. MSNA and haemodynamics were measured supine and during a graded upright tilt (30 deg for 6 min, 60 deg for 45 min or till presyncope) in 11 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

24
159
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(190 citation statements)
references
References 53 publications
(75 reference statements)
24
159
4
3
Order By: Relevance
“…A further advantage of our study was the involvement of a large group of female subjects, as the study by Smith et al only had 3 female participants. Therefore, we confirmed that the cardiovagal baroreflex sensitivity during the hypotensive stimulus is similar between sexes [6]. Variations in the menstrual cycle were not accommodated in our study; however, menstrual phase does not appear to affect the general pattern of cardiovagal unload responses [6].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…A further advantage of our study was the involvement of a large group of female subjects, as the study by Smith et al only had 3 female participants. Therefore, we confirmed that the cardiovagal baroreflex sensitivity during the hypotensive stimulus is similar between sexes [6]. Variations in the menstrual cycle were not accommodated in our study; however, menstrual phase does not appear to affect the general pattern of cardiovagal unload responses [6].…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, we confirmed that the cardiovagal baroreflex sensitivity during the hypotensive stimulus is similar between sexes [6]. Variations in the menstrual cycle were not accommodated in our study; however, menstrual phase does not appear to affect the general pattern of cardiovagal unload responses [6]. Increases in sympathetic muscle-nerve activity triggered by VM are proportional to the level of straining [1].…”
Section: Discussionsupporting
confidence: 67%
“…The phase of the menstrual cycle might alter ventilatory baroreflex mechanisms. However, recent work suggests that neither the cardiovagal nor sympathetic baroreflexes are affected by menstrual cycle (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Simulated orthostatic stress augments MSNA more during the mid-luteal phase (high estrogen and progesterone) than in the early follicular phase (low estrogen and progesterone) of the menstrual cycle. 23,24 Combined oral hormonal contraceptives in premenopausal women 25 and transdermal estrogen therapy in postmenopausal women 26 are reported not to influence the magnitude of MSNA increases elicited by orthostatic stress. The reason for such conflicting findings has yet to be resolved but difference in the mode of orthostatic challenge, the comparison of endogenous versus exogenous estrogen preparations, and confounding effects of progesterone 20 are plausible candidates.…”
Section: Discussionmentioning
confidence: 99%